Z(bus) transmission network cost allocation - Conejo, Antonio J.; Contreras, Javier; Lima, Delberis A.; Padilha-Feltrin, Antonio (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This paper addresses the problem of allocating the cost of the transmission network to generators and demands. A physically-based network usage procedure is proposed. This procedure exhibits desirable apportioning properties and is easy to implement and understand. A case study based on the IEEE 24-bus system is used to illustrate the working of the proposed technique. Some relevant conclusions are finally drawn.
Keywords: network usage; transmission cost allocation; Z(bus)